2012
DOI: 10.1002/da.22029
|View full text |Cite
|
Sign up to set email alerts
|

Periloss Dissociation, Symptom Severity, and Treatment Response in Complicated Grief

Abstract: Background Complicated grief (CG) is a bereavement-specific syndrome characterized by traumatic and separation distress lasting over 6 months. Little is known about the role of dissociation experienced during or immediately after the loss of a loved one (i.e. Peri-Loss Dissociation (PLD)) in CG. The present study aimed to examine the psychometric properties of the PLD-adapted peritraumatic dissociative experiences questionnaire and its association with symptom severity, treatment response, and drop-out rate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Our findings suggest that, to the contrary, it is the tendency to dissociate that limits the awareness of the loss and contributes to psychopathology via the impairment of the integration of the memory of the loss. Our findings are in line with former studies of dissociation and PGD that focused on PLD–the dissociation that takes place during or right after the loss–and found that higher levels of dissociation were related to an increase in PGD symptoms (Bui et al., ; Boelen, ; Boelen et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings suggest that, to the contrary, it is the tendency to dissociate that limits the awareness of the loss and contributes to psychopathology via the impairment of the integration of the memory of the loss. Our findings are in line with former studies of dissociation and PGD that focused on PLD–the dissociation that takes place during or right after the loss–and found that higher levels of dissociation were related to an increase in PGD symptoms (Bui et al., ; Boelen, ; Boelen et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…A few studies examining dissociation in the grief process have found that the loss of a close significant other in childhood was related to dissociation symptoms years later (Irwin, a,b), and recent studies examining periloss dissociation (PLD) (dissociation experienced during or right after the loss) have found a link between PLD symptoms and PGD symptoms (Boelen, Keijsers, & van den Hout, ; Bui et al., ). In addition, dissociation has been found to mediate the associations between those losses that are characterized by violence and unexpectedness, and PGD (Boelen, ).…”
mentioning
confidence: 99%
“…Bereaved controls ( n = 44) were participants without any lifetime DSM-IV disorder who reported the loss of a loved one and had an Inventory of Complicated Grief (ICG; Prigerson et al, 1995) score < 25. CG participants ( n = 28) were individuals with an ICG score ≥ 30 (Bui et al, 2013) who reported grief as their primary problem and sought treatment for CG more than 6 months after the loss (see Table 1 for participant characteristics).…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, screening of grievers at risk for developing PGD during this period is warranted. The COVID-19 pandemic is associated with specific risk factors for PGD, related to the disease itself, as well as to the measures taken to combat the spread of the virus (Mayland et al, 2020) including: immediate psychological response to the death (Bui et al, 2013) (e.g., being directly responsible for the contamination of the deceased, impaired communication between doctors and family); separation at the time of death and the absence of usual funeral rites (Mutabaruka et al, 2012) (e.g., inability "to say a last goodbye", absence of funeral rites and practices); and cooccurring environmental stressors and lack of perceived social support (Shear, 2015) (e.g., loss of employment, professional and financial insecurity, increased work burden, social isolation due to confinement measures, and uncertainty about the future). Efforts should thus be devoted to identify those at risk for developing PGD as well as PGD itself, including in primary care settings, and through health literacy promotions (e.g., by the media).…”
Section: Editorialmentioning
confidence: 99%